The effects of physical activity on cancer prevention, treatment and prognosis: A review of the literature. (June 2019) - Lugo, Diego; Pulido, Alma L.; Mihos, Christos G.; Issa, Omar; Cusnir, Mike; Horvath, Sofia A.; Lin, Jeffrey; Santana, Orlando
Highlights: Routine physical activity was found to be associated with a reduced incidence of several of the most common malignancies. The benefits of exercise in the prevention and progression of cancer patients are multiple. Physical activity reduces all-cause mortality and cancer-related mortality among patients with breast and colon cancer. Abstract: Introduction: The World Health Organization has reported that approximately 35% of cancer-related deaths are attributed to modifiable risk factors. Among the most important risk factors amenable to modification are obesity and lack of physical activity. The purpose of this article is to review the current evidence of the benefits of physical activity in various types of cancer. Methods: A PubMed search for the key words "physical activity and cancer" as well as "exercise and cancer" was used to identify all indexed publications on this topic for potential utilization in this review. One MET was defined as the amount of oxygen consumed while a person is sitting quietly and is about 3.5 mL O2/kg body weight/min. MET represents the ratio of the working metabolic rate to the resting metabolic rate. Results: Routine physical activity was found to be associated with a reduced incidence of several of the most common malignancies, including colon, breast, lung, and endometrial cancer as well as many others. Physical activity also appears to reduce all-cause mortality and cancer-related mortality among patients with breast and colon cancer, and may improve the functional status and quality of life for these patients during cancer therapy. Conclusions: The benefits of physical activity in the prevention and progression of cancer patients are multiple. However, the strength of the available evidence is limited by the observational nature of most studies. Given the probable improvement in prevention, mortality, and quality of life with structured physical activity in different malignancies, it is important that healthcare providers discuss physical activity programs with their cancer patients. Larger randomized trials are recommended.